Exclusive dealing in the presence of a vertically integrated firm; Ventas exclusivas en presencia de una empresa verticalmente integrada - Dang-Long Bui; Damiana Simanjuntak; Joe Maganga Zonda (Estudios de Economía, 2023)
This study constructs a successive Cournot model to investigate the possibility that a separated upstream input supplier can solely sell the intermediate good to a separated downstream manufacturer through an exclusive contract in the presence of a vertically integrated rival. We find that the separated firms are indifferent on whether to sign the exclusive contract or not if the downstream party is less efficient than the integrated firm in producing the final good. Next, the separated firms with an efficient downstream party are indifferent between signing or not signing, willing to sign, and not willing to sign the exclusive contract if the upstream cost differential is relatively low, medium, and high, respectively. Finally, signing such an exclusive contract does not increase consumer surplus and social welfare.
Keywords: L12; L41; L42; 330; Exclusive dealing; vertical integration; successive Cournot model